Hematology Profile of Tuberculosis Lymphadenitis Patients at Siti Rahmah Hospital, Padang, Indonesia - Debie Anggraini; Meta Zulyati Oktora (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Tuberculosis (TB) is a progressive granulomatous infectious disease caused by Gram-positive acid-resistant bacilli classified in the genus Mycobacterium. Tuberculosis in humans is caused by Mycobacterium tuberculosis (MTB) and it mainly infects the lungs, although it can also infect intestines, meninges, bones, lymph nodes, skin that cause extra-pulmonary TB. Tuberculous lymphadenitis is an inflammatory process in lymph nodes as a result of MTB activity. The inflammatory process caused by MTB activity is often associated with anemia as the most common complication. Anemia in TB is caused by an inflammatory process associated with bone marrow suppression due to pro-inflammatory cytokines, thus inhibiting the proliferation and differentiation of erythroid progenitor cells. This chronic TB infection also affects iron hemostasis, thus further affecting the hematological profile of TB patients. This study aimed to determine the hematology profile of TB lymphadenitis patients in the Siti Rahmah Hospital, Padang, Indonesia. This was a descriptive study, with a population of patients diagnosed with TB lymphadenitis based on the results of a fine needle biopsy in the Colli region. The samples of this study consisted of 24 patients who have tested the hematology profile. Tuberculosis lymphadenitis patients in females were higher than males, the mean age was 26.75±19.53 years old dominated by an adult (54%). The mean of 3 hemoglobin levels was 11.8±1.522 g/dL, with 62.5% anemia patients. The mean leukocyte count was 10400±3018.926/mm , 3 with 54.2% of patients had normal levels of leukocyte. The mean of thrombocyte count was 334750±74440.668/mm , with 83.3% in normal levels and the mean of Erythrocyte Sedimentation Rate (ESR) was 35.25±31.489 mm/h, with 54.2% patients in high ESR. Hematology profile in TB lymphadenitis patient was anemia, normal levels of leukocytes, thrombocyte, and increased levels of ESR.